Recent Advances in Research on the Human Placenta 2012
DOI: 10.5772/32346
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Imprinting in Human Placenta

Abstract: This book contains the total of 19 chapters, each of which is written by one or several experts in the corresponding field. The objective of this book is to provide a comprehensive and most updated overview of the human placenta, including current advances and future directions in the early detection, recognition, and management of placental abnormalities as well as the most common placental structure and functions, abnormalities, toxicology, infections, and pathologies. It also includes a highly controversial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 121 publications
1
8
0
Order By: Relevance
“…Rapid advancements in the discovery of integrated regulation of neuropeptide homeostasis within the brain and placenta [63, 64] have led to the concept that the placenta may be like a “third brain” linking the developed (maternal) and developing (fetal) brains [64, 65]. Maternal perturbations are conveyed to the fetus via the placenta, in the expression of transporters that regulate the flux of glucose, amino acids, and vitamins required for growth and development [66]. Thus, the placenta serves as the “master regulator” in utero and plays a highly functional role in shaping fetal development [65].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rapid advancements in the discovery of integrated regulation of neuropeptide homeostasis within the brain and placenta [63, 64] have led to the concept that the placenta may be like a “third brain” linking the developed (maternal) and developing (fetal) brains [64, 65]. Maternal perturbations are conveyed to the fetus via the placenta, in the expression of transporters that regulate the flux of glucose, amino acids, and vitamins required for growth and development [66]. Thus, the placenta serves as the “master regulator” in utero and plays a highly functional role in shaping fetal development [65].…”
Section: Methodsmentioning
confidence: 99%
“…Fetoplacental development begins with a complex and highly coordinated set of epigenetic events that take place few hours after fertilization and before the implantation of the fertilized egg [6668]. During this relatively short but very active window an almost complete reprogramming of the genome methylation takes place accompanied by a reorganization of the histone coding [68, 69].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 These findings lend support to the ''Barker hypothesis'' or the theory of developmental origins of health and disease, which hypothesizes that antenatal environmental factors lead to alterations in fetal programming that can induce permanent biological and physiologic changes later in life. [12][13][14][15][16][17][18][19] It has been hypothesized that critical windows of susceptibility exist during pregnancy, 20,21 and many of the acquired adverse effects related to the intrauterine environment result in epigenetic alterations such as changes in DNA methylation. 22 Although recent evidence has begun to show a longterm association between maternal GDM and/or preeclampsia and offspring development at birth and in childhood, [23][24][25] the underlying biological mechanism is not yet understood.…”
Section: Introductionmentioning
confidence: 99%
“…The highly controlled pattern of expression of these genes is critical to normal development and plays a particularly important role in the placenta functioning (Fowden et al 2006; Miozzo and Simoni 2002; Reik and Walter 2001). For example, loss of genomic imprinting (LOI) early in development can lead to placental and fetal growth restriction (Lambertini et al 2012a), and recent studies have shown that even relatively modest differences in imprinted gene expression are associated with fetal growth/birth weight (Kappil et al 2015a; Lambertini et al 2012b). Moreover, in both human and animal studies imprinted gene expression has been associated with exposure to a number of environmental exposures, including, maternal nutrition, alcohol use, tobacco use, and BPA exposure, and imprinted gene expression has been highlighted as a potentially useful environmental sensor (Kappil et al 2015b).…”
Section: Introductionmentioning
confidence: 99%